Akuntansi pendapatan kontrak pada PT Kumala Motor Cemerlang (Honda KMG Manado) - Leonardo Tindige; Claudia W. M. Korompis; Olivia Y. M. Sardjono (Yayasan Widyantara Nawasena Raharja, 2026)
This study evaluates the alignment of revenue accounting practices for after-sales services with PSAK 115 (Revenue from Contracts with Customers) at PT Kumala Motor Cemerlang (Honda KMG Manado). As after-sales transactions involve complex service-order cycles, ensuring precise revenue treatment is critical for financial reporting integrity in the automotive sector. Operational and accounting workflows. Data were triangulated through primary interviews with key personnel and a rigorous review of secondary sources, including service contracts, financial statements, and transaction vouchers. The results demonstrate that while the core pillars of revenue recognition and measurement largely adhere to PSAK 115, full compliance has not been achieved. Revenue recognition is appropriately triggered upon the satisfaction of performance obligations (completion of service and vehicle handover). However, a significant compliance gap exists in the disclosure domain. The company fails to provide granular information regarding contract characteristics, specific timing of performance obligation fulfillment, and the financial risks associated with customer payment delays. Additionally, the lack of explicit separation between contract assets and accounts receivable in the financial statements indicates a need for structural reporting refinements. This study underscores the necessity for automotive entities to enhance transparency in their disclosure notes to meet the rigorous demands of PSAK 115. The findings suggest that professional training and system-wide integration of contract-based accounting are essential to mitigate reporting inconsistencies.